TECHNOLOGY OF PREPARATION, TRANSFER AND PLACEMENT OF FILLING MIXTURES - Abdurahimov Abdukarim Abduhalimzoda (Galaxy International Interdisciplinary Research Journal, 2022)
Multicomponent systems based on composite binders were used in the preparation of filling mixtures. according to its composition, filling mixtures belong to the type of liquid mixtures, which made it possible to transfer them to the excavated rock cavities, under the influence of gravitational forces, through pipelines at a certain angle.